Readaptação escolar nos anos iniciais do ensino fundamental após o ensino remoto: um estudo de caso - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This study is part of the research developed by the CNPq Group for Research and Extension Language, Culture, Society and Education – LinCES –, Co-coordinated by the Advisor of this Course Conclusion Work, at the Federal University of Pampa (Unipampa), Campus Itaqui, in State of Rio Grande do Sul. The study is accredited in the field of knowledge of Human Sciences, in the area of Education, with the objective of analyzing the context(s) of school readaptation after remote teaching, and how public and private schools of the city of Itaqui/RS are facing the (non) learning of students in the initial years of Elementary School. It is commonly known that the social isolation resulting from the Coronavirus pandemic and the physical closure of schools, many parents and/or guardians were left without "alternatives" to keep their children at home and, digital technologies have become an ally in this process. In methodological terms, teachers from three schools were invited to participate in the research, two from the public system (one central and other one not central), and one from the private school. Nine teachers agreed to participate. For the analysis of the collected data, the Content Analysis (CA) of Bardin (2011) was used as a way of apprehending the signs of the content given by a priori categories, as well as the emerging meanings in the interpretation and systematization of the social phenomenon studied. The "findings" of the research, can be seen that they exceed expectations, even though a pessimistic picture is drawn in terms of students non-learning, as well as what implies psychological and/or behavioral problems, schools are looking for alternatives for the recovery of children's education (in its integral sense), after all, they are starting their respective schooling itineraries. The acceptance of ICT in face-to-face teaching, even as a complement to homework, has been a reality among almost all the interlocutor teachers, as they believe that they will remain as a complement to pedagogical practices inside and outside the classroom.
Keywords: TIC; Readaptação; Ensino remoto; Anos iniciais do ensino fundamental; Information and communication technology; Readaptation; Remote teaching; Early years of elementary school; CNPQ::CIENCIAS EXATAS E DA TERRA